2013
DOI: 10.1155/2013/675264
|View full text |Cite
|
Sign up to set email alerts
|

Development of Glass/Jute Fibers Reinforced Polyester Composite

Abstract: Composites play significant role as engineering material and their use has been increasing day by day due to their specific properties such as high strength to weight ratios, high modulus to weight ratio, corrosion resistance, and wear resistance. In present work, an attempt is made to hybridize the material using synthetic (glass) as well as natural fibres (chemically treated jute), such that to reduce the overall use of synthetic reinforcement, to reduce the overall cost, and to enhance the mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 10 publications
2
32
1
1
Order By: Relevance
“…Siddika et al [31] reported the effect of chemical treatment of fibre on jute-coir fibre reinforced hybrid polypropylene composites by 5 % NaOH treatment shows an improving trend of mechanical properties. Similar effect was observed in glass/jute reinforced polyester [32] and in ramie-glass fibre reinforced polymer matrix hybrid [33].…”
Section: Introductionsupporting
confidence: 81%
“…Siddika et al [31] reported the effect of chemical treatment of fibre on jute-coir fibre reinforced hybrid polypropylene composites by 5 % NaOH treatment shows an improving trend of mechanical properties. Similar effect was observed in glass/jute reinforced polyester [32] and in ramie-glass fibre reinforced polymer matrix hybrid [33].…”
Section: Introductionsupporting
confidence: 81%
“…In this study, AESO modified epoxy resin reinforced with four-ply jute woven fabrics and are produced by the vacuum infusion method. When literature is examined, it is seen that mostly four, six, eight and ten plied fabric reinforced composite plates were produced [35][36][37][38][39][40][41][42][43][44][45]. Since the main aim of this study is to investigate the effect of bio-resin ratio on the properties of composite material, the minimum number of fabric layers (4) is chosen.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline, peroxide, permanganate, silane, acetylation, benzoylation, etc. are quite common surface treatments executed by several researchers over a period of time .…”
Section: Introductionmentioning
confidence: 99%